Strengthening Financial Governance at Rt 07 Rw 03 Level, Krendang Village, Tambora District, West Jakarta - Muhammad Aras Prabowo; Bayu Rahman; Siti Danila Hanipa (Innovation Business Management and Accounting Journal, 2025)
The research objective of this service activity is to improve the skills and knowledge of RT administrators in managing finances effectively and transparently, so that they are able to record and report financial transactions better using tools such as Microsoft Excel. This article presents community service activities in the form of financial management training for RT (Rukun Tetangga) in Tambora District, West Jakarta. The training aims to improve the skills and knowledge of RT administrators in managing finances effectively and transparently. The training method consists of four stages, namely socialization, practice, monitoring and evaluation. The results of the training show that residents better understand the concept of financial management and can apply it in practice. They can also use Microsoft Excel to create simple worksheets for recording and reporting financial transactions. This training was well received by residents and was considered a success.